2015
DOI: 10.3177/jnsv.61.382
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Deficiency Increases Serum Concentrations of Parathyroid Hormone through a Decrease in Serum Calcium and Induces Bone Fragility in Rats

Abstract: SummaryWe hypothesized that a zinc-deficient diet alters the mineral (calcium, magnesium, and phosphorus) components of bones, as well as hormones related to bone remodeling, and negatively affects bone metabolism. Four-week-old male Wistar rats were randomly assigned to one of three groups for 4 wk: a zinc-adequate group (C, 30 ppm); a zinc-deficient group (ZD, 1 ppm); and a pair-fed group (PF, 30 ppm), which was pair-fed to the ZD group. Bone mineral density and bone mechanical properties were reduced in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 52 publications
2
23
0
1
Order By: Relevance
“…2,3) Furthermore, we previously observed that long-term (4 weeks) zinc deficiency decreases bone formation and increases bone resorption, resulting in bone loss. 4) Although several studies have proved that zinc deficiency leads to the development of osteoporosis 5,6) , few studies have attempted to examine the effect of short-term dietary zinc deficiency on bone metabolism.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2,3) Furthermore, we previously observed that long-term (4 weeks) zinc deficiency decreases bone formation and increases bone resorption, resulting in bone loss. 4) Although several studies have proved that zinc deficiency leads to the development of osteoporosis 5,6) , few studies have attempted to examine the effect of short-term dietary zinc deficiency on bone metabolism.…”
mentioning
confidence: 99%
“…The experimental diets were prepared as described in a previous study. 4) After 1 week of treatment, the rats were fasted for 12 h, were then anesthetically sacrificed for dissection, and blood and femur samples were collected for analysis. These studies were approved by the Animal Studies Committee of Tokyo University of Agriculture, and all procedures involving rats were conducted in accordance with the guidelines for the Care and Use of Laboratory Animals of Tokyo University of Agriculture.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The skeleton is a reserve of calcium which is drawn upon to maintain adequate serum calcium when calcium intake is limited. Elevated PTH stimulates bone resorption and release of bone calcium for restoring serum calcium concentration, a process that ultimately causes a decrease in BMD [29] (Figure 5). If LZG had continued to be fed a low zinc diet, the calcium deficiency of rat would have been more severe.…”
Section: Relationship Between Zinc Deficiency Calcium Metabolism Andmentioning
confidence: 99%
“…Цинк служит коферментом для многих металлоферментов и участвует в регуляции активности остеобластов, синтеза коллагена и активности щелочной фосфатазы. Дефицит цинка может сопровождаться снижением всасывания кальция в кишечнике и повышением уровня паратгормона, который активирует костный обмен [46]. В одном исследовании средние сывороточные концентрации цинка у женщин с остеопорозом были значительно ниже, чем у женщин с остеопенией или здоровых женщин [47].…”
Section: профилактика переломовunclassified